MEMBANGUN PERILAKU KONSUMSI MELALUI PENGETAHUAN KONSUMEN BERBASIS KOMUNITAS (SUATU KAJIAN LITERATUR) - Nova Sillia; James Hellyward; Jafrinur Hellyward; Melinda Noer (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2017)
The purpose of this study was to understand the concept of knowledge and the consumption behavior creation through the consumer knowledge-based community. This paper obtained by read, summarize andsynthesize book and article obtained from international and national journals. The results of this literature review showed that consumer knowledge is a major factor to create the consumption behavior. Various efforts to increase knowledge has been done through a variety of sources and media-based individuals, corporations and governments. It is not effective to create consumption behavior. Consumers will be motivated to behave because their belief to the information sources. Community is a medium for consumers to share their experiences. Therefore, community cancreate consumption behavior effectively.